HUBUNGAN FILSAFAT, ILMU PENGETAHUAN, ILMU ADMINISTRASI DAN FILSAFAT ILMU ADMINISTRASI PUBLIK - Yahya Antu; Juliko Suleman; Yana Yanti Suleman; Nurcholis Suleman; Hasim (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
Philosophy, science, knowledge, and administrative science are interrelated concepts and are the basis for the development of public administration science. This relationship reflects how philosophical foundations influence the development of science in general and public administration in particular. In this context, philosophy provides an epistemological, ontological, and axiological foundation for science. Science, as a result of the development of philosophy, uses a systematic approach to understanding phenomena in the universe. Knowledge, as a product of human interaction with the environment, becomes the raw material for science. Meanwhile, the science of public administration, which is in the realm of applied social sciences, integrates philosophical and knowledge approaches to understand and solve problems of government and public service. In this context, the development of a philosophy of public administration that is oriented towards universal values, such as justice, efficiency, and accountability, becomes very important. This will not only strengthen the theoretical foundation of public administration science, but also increase its relevance and effectiveness in facing practical challenges in society. Thus, a comprehensive understanding of the relationship between philosophy, science, knowledge, administrative science, and the philosophy of public administration is not only relevant for the development of this science, but also for the improvement of the quality of public policy and governance as a whole.This research emphasizes the relationship between philosophy, science, knowledge, administrative science, and the philosophy of public administration science has significant relevance in answering contemporary challenges. In an era characterized by rapid change, a philosophy-rooted approach allows public administration to remain relevant, responsive, and oriented to the interests of society. By integrating philosophical, empirical, and practical approaches, public administration science can contribute to the creation of fair, efficient, and inclusive policies, thereby improving the quality of people's lives in the midst of the complexity of the modern world.